STUDY OF BODILY AWARENESS DURING A PSYCHOLOGICAL INQUIRY - Dunaeva, Victoria (PEOPLE: International Journal of Social Sciences, 2018)
In the last few decades there have been an increasing number of studies on mental health and emotional well-being and their influence on physical health. According to this approach, physical problems often manifest unexpressed hidden inner conflicts. Psychologists increasingly apply their client's awareness of bodily sensations as a tool for therapy. In my paper I would like to present one of such psychological methods named focusing which I use in my practice as a clinical psychologist. Focusing method was elaborated by Eugene Gendlin, American philosopher, who collaborated with the founder of person-centered therapy Carl Rogers. Gendlin’s research showed that positive change in psychotherapy depended on client’s ability to experience bodily reaction of the topics discussed during therapy. In my practice I include Focusing method into my own system based on the idea that we can influence our healing process by discovering inner resources. It becomes possible when we get rid of feeling guilty and feeling of "being wrong" and overcome a negative self-image created as a result of adverse childhood .I have found that the awareness and verbalization of negative feelings facilitate the process of releasing emotional suffering from the memory of the body. Specific bodily responses can lead to discovering the true reasons of emotional conflicts. I would like also to show how I combine the Focusing approach with another psychological method based on the connection of body and mind, Recall Healing elaborated by Canadian expert in holistic approach to health Gilbert Renaud.